The application of using time-driven activity-based costing in product operation and service operation - Sri Nur Areena, Mohd Zaini (2021)
Two deeply connected principles consist of products and services which most products actually have a service aspect. The product is an operation that can be point at, while the service is any activity which have intangible characteristics. Nevertheless, there are three objectives in this work which related to problem statements in both operations. In current practise of costing method in palm oil plantation and academic library, there are almost no establishment of time equation to interpret deviation of activities. The method do not implement time equation so processing time determined by company and organization are not in accordance with actual processing time in work station. Then, the current practise do not illustrate the correlation between supplied resources and practical capacity. It is important to develop capacity cost rate (CCR) in order to interpret it in form of unused capacity. Other than that, it is not necessarily proved that data extraction of time equation and CCR in service operation is easily accessible, while data extraction in product operation is more difficult to obtain. The purpose of this study is to compare the Time-driven Activity-based Costing (TDABC) application between product and service operation through selected criteria. For product operation, this work conducted at palm oil plantation Simpai Division 1 Estate in Prosper Palm Oil Mill Sdn. Bhd. which located in Muadzam Shah, Pahang. The estate is divided into three activity centers which are nursery, replanting and ramp. For service operation, data collection of academic library are taken in Universiti Malaysia Pahang. However, in this work only two activity centers are been discussed which are acquisition and cataloging. The analysis of the data is using four steps of TDABC method which are process mapping, time equation, CCR and forecast analysis. Eventually, in product operation, the total used time in all three activity centers of palm oil plantation are 3,220,928.04 minutes for mature area and 2,390,513.94 minutes for immature area. The total used capacity are RM6,041,995.10 for mature area and RM5,591,587.73 for immature area. In mature and immature area, the total unused time are 170,188 and 100,450.50 minutes respectively. Whereas, the insufficient time are -2,241,951.04 and -1,683,844.44 minutes for mature and immature separately. Then, the unused capacity in mature and immature area are RM4,500,806.30 and RM4,248,485.33. On the other hand, in service operation, the total used time are 39,932.73 minutes for local material and 29,571.82 minutes for oversea material. The total used capacity in both local and oversea materials are RM47,667.61 and RM16,876.28 respectively. The total unused time are 5,681.92 and 12,892.88 minutes in local and oversea material respectively. Whereas for local and oversea material, the total insufficient time are -3,374.65 and -224.70 minutes accordingly. The unused capacity are RM40,960.02 and RM144,202.51 in local and oversea material respectively. Ultimately, in terms of unused capacity, there are no significant differences when applying TDABC in product and service operation. Whereas, in terms of process dependency, activities in product operation is dependent to one another. While activities in service operation is independent. In a nutshell, TDABC is a model which can analyzed idle capacity and design strategies towards maximization of organization’s value.